2019
DOI: 10.1177/1077558719888427
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Outcomes of Burnout Among Primary Care Providers in the United States: A Systematic Review

Abstract: Primary care providers (PCPs) in the United States work in challenging environments and may be at risk for burnout. This article identifies the predictors and outcomes of burnout among PCPs in the United States. A comprehensive literature search of eight databases was conducted to identify studies investigating predictors or outcomes of PCP burnout. The Joanna Briggs Institute’s critical appraisal checklists for cross-sectional and cohort studies were used for quality appraisal. Overall, 21 studies met inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 54 publications
3
77
0
Order By: Relevance
“…Since this time, this research field has flourished with numerous further original studies being reported. This growth has enabled the subsequent publishing of reviews focused on specific professional groups such as physicians and primary healthcare providers [ 68 , 69 ]. It has also allowed for a wider range of patient care outcomes to be synthesised including provider communication and quality of care indicators [ 68 70 ].…”
Section: Consequences Of Burnoutmentioning
confidence: 99%
“…Since this time, this research field has flourished with numerous further original studies being reported. This growth has enabled the subsequent publishing of reviews focused on specific professional groups such as physicians and primary healthcare providers [ 68 , 69 ]. It has also allowed for a wider range of patient care outcomes to be synthesised including provider communication and quality of care indicators [ 68 70 ].…”
Section: Consequences Of Burnoutmentioning
confidence: 99%
“…This finding is consistent with reports of higher levels of burnout among the primary care workforce and a robust economy that bolstered retirement funds. [18][19][20] The estimated shortage of about 14,900 Primary Care physicians in 2018 is based on the calculation from the Health Resources and Services Administration (HRSA) that about this number of primary care providers are needed to remove the primary-care-shortage designation in currently designated shortage areas. Each modeled supply and demand scenario is based on assumptions about the continuation of current trends or changes in care delivery that might happen at a future date, so each scenario has a degree of uncertainty.…”
Section: Total Physician Supply and Demandmentioning
confidence: 99%
“…In particular is concern that rising levels of provider burnout could contribute to earlier retirement. [77][78][79][80][81][82][83] Scenarios simulating a one-or two-year shift in retirement patterns can make it easier to understand the effect this may have on the overall supply of a health profession.…”
Section: Scenariosmentioning
confidence: 99%